Thermogravimetric analysis and kinetic modeling of low-transition-temperature mixtures pretreated oil palm empty fruit bunch for possible maximum yield of pyrolysis oil - Yiin, C.L. (Elsevier Ltd, 2018)
The impacts of low-transition-temperature mixtures (LTTMs) pretreatment on thermal decomposition and kinetics of empty fruit bunch (EFB) were investigated by thermogravimetric analysis. EFB was pretreated with the LTTMs under different duration of pretreatment which enabled various degrees of alteration to their structure. The TG-DTG curves showed that LTTMs pretreatment on EFB shifted the temperature and rate of decomposition to higher values. The EFB pretreated with sucrose and choline chloride-based LTTMs had attained the highest mass loss of volatile matter (78.69 and 75.71) after 18 h of pretreatment. For monosodium glutamate-based LTTMs, the 24 h pretreated EFB had achieved the maximum mass loss (76.1). Based on the Coats-Redfern integral method, the LTTMs pretreatment led to an increase in activation energy of the thermal decomposition of EFB from 80.00 to 82.82â94.80 kJ/mol. The activation energy was mainly affected by the demineralization and alteration in cellulose crystallinity after LTTMs pretreatment. Â© 2018 Elsevier Ltd